Conservative Fashion Magazines in the Context of Consumption Culture in Turkey A Comparison of Conservative and Secular Fashion Magazines with the Case of Aysha and Elle - Aydın Kaymak; Mehmet Emin Babacan (İnsan & Toplum)
Conservative fashion magazines dealt with in different ways by different disciplines, social and historical process taking place in Turkey, is important as an area of political and economic change can be monitored in an open manner. In this context, the main subject of the study is to consider conservative fashion magazines within the framework of consumer culture. In addition, the aim of this study is to reveal the similarities and differences between conservative fashion magazines and secular fashion magazines in terms of consumption culture. For this reason, Aysha and Elle journals were chosen as samples. The issues of the related journals published in 2016 were handled in line with the consumption messages they covered. The journals were analyzed with quantitative content analysis method in order to decipher the consumption messages in the texts. In the study, “What is the ratio of articles containing consumption messages to the total text type?”, “What is the subject distribution of articles containing consumption messages?”, “How much are consumption messages in magazines?”, “What are the similarities and differences between Aysha and Elle?” answers are sought. In the study, it is concluded that the ratio of articles containing consumption messages to Aysha magazine is 70%, the subjects of articles containing consumption messages are generally product, space promotion and fashion, and there are intensive consumption messages in the magazine. In addition, in the context of consumer culture, it was found that Aysha magazine was not very different from Elle fashion magazine, except for some basic differences.